Implementasi Metode WP Dan TOPSIS Dalam Menentukan Perbaikan Alat Berat : Studi kasus: PT.Pilaren - Ariyanto, Arya; Samsudin; Dedi Irawan, Muhammad (Institut Teknologi Garut, 2025)
This study aims to implement the WP and TOPSIS methods in the decision-making process for heavy equipment repairs at PT. Pilaren. The WP method is used to assign weights to various criteria such as damage condition, operational impact, spare parts availability, repair costs, and other factors to determine the best alternative in a non-linear manner. Meanwhile, the TOPSIS method helps to assess the alternatives that are closest to the ideal solution and furthest from the worst solution objectively. A web-based decision support system was developed using the Laravel framework and MySQL database to facilitate data management and calculation processes. The results of this system are expected to improve efficiency, transparency, and objectivity in determining the priorities for heavy equipment repairs in the company.